Generalisability of vaccine effectiveness estimates: an analysis of cases included in a postlicensure evaluation of 13-valent pneumococcal conjugate vaccine in the USA. Issue 8 (28th August 2017) - Link-Gelles, Ruth; Westreich, Daniel; Aiello, Allison E; Shang, Nong; Weber, David J; Rosen, Jennifer B; Motala, Tasneem; Mascola, Laurene; Eason, Jeffery; Scherzinger, Karen; Holtzman, Corinne; Reingold, Arthur L; et al.
Abstract : Objectives: External validity, or generalisability, is the measure of how well results from a study pertain to individuals in the target population. We assessed generalisability, with respect to socioeconomic status, of estimates from a matched case–control study of 13-valent pneumococcal conjugate vaccine effectiveness for the prevention of invasive pneumococcal disease in children in the USA. Design: Matched case–control study. Setting: Thirteen active surveillance sites for invasive pneumococcal disease in the USA. Participants: Cases were identified from active surveillance and controls were age and zip code matched. Outcome measures: Socioeconomic status was assessed at the individual level via parent interview (for enrolled individuals only) and birth certificate data (for both enrolled and unenrolled individuals) and at the neighbourhood level by geocoding to the census tract (for both enrolled and unenrolled individuals). Prediction models were used to determine if socioeconomic status was associated with enrolment. Results: We enrolled 54.6% of 1211 eligible cases and found a trend toward enrolled cases being more affluent than unenrolled cases. Enrolled cases were slightly more likely to have private insurance at birth (p=0.08) and have mothers with at least some college education (p<0.01). Enrolled cases also tended to come from more affluent census tracts. Despite these differences, our best predictive model for enrolment yielded a concordance statistic of only 0.703, indicating mediocre predictive value. Variables retained in the final model were assessed for effect measure modification, and none were found to be significant modifiers of vaccine effectiveness. Conclusions: We conclude that although enrolled cases are somewhat more affluent than unenrolled cases, our estimates are externally valid with respect to socioeconomic status. Our analysis provides evidence that this study design can yield valid estimates and the assessing generalisability of observational data is feasible, even when unenrolled individuals cannot be contacted.